Extrusion of a Cochlear Implant Positioner Through the Tympanic Membrane in a Pediatric Patient: Management of a Delayed Complication. (August 2014) - Dhillon, Vaninder K.; Hoa, Michael; Winter, Margaret; Wilkinson, Eric P.
Objective: This study aimed to present a case of an extruded Advanced Bionics positioner, with the goal of educating a new generation of otologic surgeons on management of the delayed complications associated with this cochlear implant model. Methods: Retrospective case report in a pediatric patient. Results: We observed the extrusion of an Advanced Bionics positioner 10 years after cochlear implantation. Conclusion: Awareness of the Advanced Bionics positioner as a component of certain historical models of cochlear implants is important as the delayed complications associated with this model may still be encountered. Management of an extruded positioner should include precautions against infectious complications, repair of the defect, and assessment of the patient's performance with the cochlear implant.